Screening Method to Identify Watermelon Cultivars Resistant to Acidovorax citrulli, the Cause of Bacterial Fruit Blotch - Lee, Soo Min; Kim, Gahyeon; Kim, Hun; Choi, Gyung Ja (The plant pathology journal, 2024)
Acidovorax citrulli is a causative pathogen for bacterial fruit blotch (BFB) in Cucurbitaceae, including watermelon. The most effective method to control this plant disease is to cultivate resistant cultivars. Herein, this study aimed to establish an efficient screening method to determine the resistance of watermelon cultivars against A. citrulli. To this end, we explored the virulence of seven A. citrulli isolates belonging to clonal complex group I or II based on gltA gene analysis. Furthermore, we evaluated the BFB occurrence in the seedlings of two arbitrarily selected watermelon cultivars according to the growth stage of the watermelon seedlings, inoculum concentration, and incubation temperature after inoculation in a humidity chamber. Taken together, we established the following method to determine the resistance of watermelon cultivars against A. citrulli: watermelon seedlings at the fully expanded two-leaf stage can be spray-inoculated with an A. citrulli bacterial suspension at a concentration of 1.0 × 106 cfu/ml; after incubation for 48 h at 28℃ in a humidity chamber, the plants were cultivated in a growth chamber at 25℃ with 80% relative humidity under a 12-h light/dark cycle; and BFB occurrence on the plants can be investigated at 7 dpi by visual estimation of the diseased leaf area (%). Based on these experimental methods, we investigated the resistance degree of 43 commercial watermelon cultivars against A. citrulli KACC 17005. Therefore, our results can provide important information for the development of resistant cultivars against A. citrulli.